Pengaruh Model Pembelajaran Kooperatif Tipe Team Games Tournament (TGT) Terhadap Hasil Belajar Siswa - Fauzi, Akhmad; Masrupah, Syiraful (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2024)
Education is the most important part for every individual in increasing their knowledge. Education in Indonesia is currently not said to be good, especially in mathematics education. The use of methods that can generate enthusiasm for learning is indeed important, such as the TGT-type cooperative learning method that combines games and tournaments in learning. The purpose of this study is to determine the implementation and influence of the Team Games Tournament (TGT) type cooperative learning model on the learning outcomes of grade IV students in plan figure mathematics subjects at MI Miftahul Ulum Pandanarum. Using a type of research two group pre-test post-test design. With a class IV research sample of 50 students. In the implementation of the team games tournament (TGT) type cooperative learning model, data analysis obtained that the average learning outcomes of experimental class students were 77.4 while the control class was 57.6, so the average score of experimental class students was better than in the control class.